Anxiety and Psycho-Physiological Stress Response to Competitive Sport Exercise - Tanguy, Gaelle; Sagui, Emmanuel; Fabien, Zagnoli; Martin-Krumm, Charles; Canini, Frédéric; Trousselard, Marion (Frontiers in Psychology, 2018)
Introduction: Sport is recognized as beneficial for health. In certain situation of practice, it nevertheless appears likely to induce a stress response. Anxiety is a stress response-modulating factor. Our objective is to characterize the role of anxiety in the stress response induced by a selective physical exercise. Method: Sixty-three young male military conducted a selective sporting running event (a 8-km commando-walk) and were recorded the day before, the day of the race, and the day after. The variables were psychometric [personality questionnaires, coping and anxious/stress state, and physiological (nocturnal heart rate variability and actigraphy)]. The subjects were classified, using scores on anxiety questionnaires at baseline, into two groups according to their anxious (G ANX) or non-anxious (G N-ANX). Results: Before the race, the G ANX was characterized by a lower level of self-esteem, higher scores in dysfunctional coping and a greater perceived stress compared to the G N-ANX. Compared to G N-ANX, the stress response to the exercise was higher in G ANX: G ANX exhibited (Selye, 1950) in immediate post-exercise, greater level in activation markers, and mental fatigue associated with a same level of physical fatigue and (Kim et al., 2018) in nocturnal post-exercise, an increase in sympathetic activation associated with a higher sleep fragmentation. Conclusion: A competition selection sport exercise causes a stress response, particularly for anxious subjects. Anxious status could be involved in the risk of emergence of overtraining in sport practice. These results must be taken into account when sport practice is used for anxiety management.